(untitled) (CAHIERS MAGELLANES-NS, 2024)
Urban green spaces play a critical role in enhancing the quality of life in rapidly growing metro cities. This study examines the relationship between green space accessibility, utilization, and perceived benefits to urban residents' overall well-being in major Indian metros. Utilizing a mixed-method approach, data were collected through surveys, interviews, and geospatial analysis to understand usage patterns, accessibility barriers, and their impact on physical and mental health. Statistical analyses, including correlation, regression, and ANOVA, revealed significant positive associations between frequent green space visits, proximity, and improved quality of life. Despite these benefits, challenges such as poor maintenance, safety concerns, and time constraints hinder optimal utilization. The findings underline the urgent need for urban planning strategies prioritizing green infrastructure to foster a healthier, more sustainable urban environment. This study provides actionable insights for policymakers to bridge the gap between green space availability and equitable accessibility in India’s bustling metro cities.